The impact of prostate volume estimation on the risk-adapted biopsy decision based on prostate-specific antigen density and magnetic resonance imaging score - Baudewyns, Arthur; Guenzel, Karsten; Halinski, Adam; Dariane, Charles; Delavar, Gina; Anract, Julien; Barry Delongchamps, Nicolas; Jabbour, Teddy; Bourgeno, Henri-Alexandre; Lefebvre, Yolène; Ferriero, Mariaconsiglia; Simone, Giuseppe; et al. (World journal of urology, 2024)
PURPOSE: Utility of prostate-specific antigen density (PSAd) for risk-stratification to avoid unnecessary biopsy remains unclear due to the lack of standardization of prostate volume estimation. We evaluated the impact of ellipsoidal formula using multiparametric magnetic resonance (MRI) and semi-automated segmentation using tridimensional ultrasound (3D-US) on prostate volume and PSAd estimations as well as the distribution of patients in a risk-adapted table of clinically significant prostate cancer (csPCa). METHODS: In a prospectively maintained database of 4841 patients who underwent MRI-targeted and systematic biopsies, 971 met inclusions criteria. Correlation of volume estimation was assessed by Kendall's correlation coefficient and graphically represented by scatter and Bland-Altman plots. Distribution of csPCa was presented using the Schoots risk-adapted table based on PSAd and PI-RADS score. The model was evaluated using discrimination, calibration plots and decision curve analysis (DCA). RESULTS: Median prostate volume estimation using 3D-US was higher compared to MRI (49cc[IQR 37-68] vs 47cc[IQR 35-66], p < 0.001). Significant correlation between imaging modalities was observed (τ = 0.73[CI 0.7-0.75], p < 0.001). Bland-Altman plot emphasizes the differences in prostate volume estimation. Using the Schoots risk-adapted table, a high risk of csPCa was observed in PI-RADS 2 combined with high PSAd, and in all PI-RADS 4-5. The risk of csPCa was proportional to the PSAd for PI-RADS 3 patients. Good accuracy (AUC of 0.69 and 0.68 using 3D-US and MRI, respectively), adequate calibration and a higher net benefit when using 3D-US for probability thresholds above 25% on DCA. CONCLUSIONS: Prostate volume estimation with semi-automated segmentation using 3D-US should be preferred to the ellipsoidal formula (MRI) when evaluating PSAd and the risk of csPCa.
Keywords: klinické rozhodování; Prostatic Neoplasms; Magnetic Resonance Imaging; prostata; nádory prostaty; velikost orgánu; ultrazvukem navigovaná biopsie; magnetická rezonanční tomografie; Humans; lidé středního věku; multiparametrická magnetická rezonance; Aged; Image-Guided Biopsy; Prostate-Specific Antigen; senioři; lidé; Male; Prostate; Middle Aged; Clinical Decision-Making; prostatický specifický antigen; Multiparametric Magnetic Resonance Imaging; Organ Size; Risk Assessment; mužské pohlaví; prospektivní studie; hodnocení rizik; Prospective Studies